Arjunasahasrabāhu Across Cultures: Textual Transmission and Religious Reorientation from India to Java-Bali - Zakariya Pamuji Aminullah (POETIKA, 2026)
How did the figure of Arjunasahasrabāhu/Kārtavīryārjuna travel from Sanskrit sources to Java and Bali, and what does his trajectory reveal about the formation of “Hindu-Buddhist Nusantara”? This article reads three textual layers: the Sanskrit Rāmāyaṇa-Uttarakāṇḍa and selected Purāṇas (Vāyu, Nārada); the Old Javanese Uttarakāṇḍa (ca. 996–1016 CE); and Mpu Tantular’s Kakavin Arjunavijaya (1379 CE), together with representative texts from the Balinese Rāmāyaṇa-Uttarakāṇḍa corpus. The study combines philological reading with the framework of cultural ecology—the material, social, and symbolic conditions in which texts are produced and received—and asks, at each transition, three questions: which features of the figure persist, which are erased, and which are reoriented? In Sanskrit sources, Arjunasahasrabāhu stands at the intersection of Candravaṃśa genealogy, Śaiva-Vaiṣṇava theology, and varṇa politics. In the Old Javanese Uttarakāṇḍa, the śaiva-bhairava idiom is preserved but reframed within the rājapūjaka ecology of Early Mataram. In Kakavin Arjunavijaya, he becomes a Majapahit nāyaka within a Śiva-Buddha cosmological synthesis. In the Balinese corpus, he develops into an autonomous heroic and didactic figure across multiple kakavin. The case shows that “Hindu-Buddhist Nusantara” emerged through a layered recomposition across distinct cultural ecologies, contributing to current debates on Indianization, the literary history of Java and Bali, and the comparative religious history of Southeast Asia.